Executive compensation and risk taking - Patrick Bolton; Hamid Mehran; Joel Shapiro (Federal Reserve Bank of New York, 2010)
This paper studies the connection between risk taking and executive compensation in financial institutions. A theoretical model of shareholders, debtholders, depositors, and an executive suggests that 1) in principle, excessive risk taking (in the form of risk shifting) may be addressed by basing compensation on both stock price and the price of debt (proxied by the credit default swap spread), but 2) shareholders may be unable to commit to designing compensation contracts in this way and indeed may not want to because of distortions introduced by either deposit insurance or naive debtholders. The paper then provides an empirical analysis that suggests that debt-like compensation for executives is believed by the market to reduce risk for financial institutions.
Keywords: G21; G34; 330; Executive compensation; risk taking